Faktor-Faktor yang Berhubungan dengan Partisipasi Pria dalam Program Keluarga Berencana di Kabupaten Muaro Jambi - Yun Afrinaldi; Suandi Suandi; Syafri Syafri (PERSPEKTIF, 2021)
This paper aims to gain an understanding of the characteristics of male couples of childbearing age, their participation in the family planning program and to assess the factors that influence men's participation in the family planning program in Muaro Jambi District. The problem in this study is focused on the low rate, where in 2018 only 1.3% consisted of 1.2% condom acceptors and 0.1% vasectomy acceptors (MOP). This achievement is very far behind when compared to the Jambi Province coverage of 2.5%. This condition illustrates the low participation of men in the family planning program in Muaro Jambi Regency. In order to approach this problem a reference is used from several factors that influence the low proda participation in the family planning program, including predisposing factors, supporting factors and driving factors. The data were collected through a direct interview survey to respondents using a questionnaire and analyzed using a quantitative method with a cross sectional design approach. This study concludes that knowledge is the most dominant factor associated with male participation in family planning programs in Muaro Jambi District. Men with good knowledge about family planning were 2.037 times more likely to participate in family planning programs than men with knowledge